Compromised root development constrains the establishment potential of native plants in unamended alkaline post-mining substrates - Cross, Adam; Stevens, J.; Sadler, R.; Moreira-Grez, B.; Ivanov, D.; Zhong, H.; Dixon, Kingsley; Lambers, H. (Springer, 2018)
© 2018, Springer Nature Switzerland AG. Background and aims: Mined materials often require rehabilitation or ecological restoration through revegetation as part of mine closure and relinquishment practices, yet there is a widening gap between the expectations of recovery and what industry achieve. The edaphic conditions of post-mining substrates present a suite of potential limitations to plant growth and may constrain the establishment capability and development of native species. Methods: We assessed seedling emergence, relative growth rate and calculated standardised growth estimates using 10 measured root and shoot parameters for six locally-dominant native species from different families and nutrient-acquisition strategies in a range of representative mining restoration substrates (topsoil, tailings, capped tailings and waste rock), examining their suitability as pioneers for ecological restoration. Results: The establishment and growth of all six species in post-mining substrates were significantly compromised. Root development was significantly responsive to substrate, with measured root parameters on average 27% lower in capped tailings, 41% lower in waste rock and 67% lower for individuals grown in tailings compared with those grown in topsoil alone. Plant growth was compromised at different life cycle stages (seed germination, seedling establishment, early growth and development) and across a number of different traits, with primary edaphic constraints including high pH (>8.5) and insufficient available N. The highest-performing species on post-mining substrates was an N2-fixing legume, while lowest-performing species included those with ectomycorrhizal associations or no specific nutrient-acquisition strategy. Conclusions: Edaphic filters may be significant drivers of trajectory and success in rehabilitation and restoration projects at scales ranging from individuals (by limiting establishment or constraining growth and development) to communities (by causing species to assemble in a different manner than the desired reference community). If intractable edaphic parameters constraining plant establishment and early development such as extreme pH and a lack of available nutrients are not ameliorated, the restoration trajectory on post-mining landforms is likely unfavourable. Failure to adequately ameliorate post-mining substrates may represent a major liability for industry in meeting mine-closure requirements.